PENYUSUNAN TATA BAHASA MELAYU BENGKULU - Supadi, Supadi (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
The purpose of this research is to arrange Bengkulu Malay Grammar. Research method used in this research was descriptive method. Observation, interview, recording and writing on data carts were techniques used in collecting data. Distributional analysis method was used in this research.  The results of this research indicate that from the point of phonology, there is a minimum pair, for example: /c/ and /d/ in /capek/ ‘tired’ and /dapek/ ‘to get’ /m/ and /b/ on /male/ ‘lazy’ and /bale/ ‘revenge’ ; consonant distribution and vowel, for example: [p] on [pai] ‘go’ and [dapek] ‘to get’, [idup] ‘life’, [i] on [iko] ‘ini’, [bini] ‘istri’, [aRi] ‘day’; semivowel, for example duo [duwo] ‘two’, dia [diyo] ‘he/she’. From the point of morphology studied were reduplication, morphophonemic, and word cluster. Reduplication was grouped into two categories, firstly total reduplication, for example, cepek-cepek ‘in a rush’ and secondly part reduplication, for example, termenung-menung, and ‘meditate’. The studied  morphophonemic is a phoneme change, for example, N- + baco   mbaco ‘to read’ and phoneme adding, for example, N- + cat   ngecat ‘ to paint’. Word cluster in this research covers nominal adjectival, adverbial, numerical, verb, pronominal, preposition, conjunction, interrogative, and interjection. From the point of syntax studied were clause, sentence. The studied sentences in this research include informational, interrogative, command, and negation, active and passive sentence.